Study of melanocyte density and epidermal thickness in vulvar lichen sclerosus lesions - Fu, Yu; Bao, Yingqiu; Li, Ziyuan; Gao, Xiaoman; Chang, Jianmin (International journal of dermatology, 2021)
Objective This study aimed to analyze changes in melanocyte density and epidermal thickness in vulvar lichen sclerosus (VLS). Methods Vulvar skin tissues were collected from 15 VLS female patients in Beijing Hospital, classified into early (n = 7) and late VLS (n = 8) groups according to pathological manifestations. Melanocyte density and full epidermal and cell‐layer (from the bottom of the stratum corneum to that of the basal layer) thickness were calculated using an image analysis software. The control group was normal vulvar skin tissues from 15 females after plastic surgery. Results The early VLS (0.170 ± 0.071 µm) and late VLS (0.110 ± 0.035 µm) groups had significantly lower densities of epidermal melanocytes than the control group (0.275 ± 0.036) (F = 36.426, P < 0.001). The cell‐layer thickness did not differ between the early VLS (154.603 ± 121.984 µm) and control (176.974 ± 80.296 µm) groups (P = 0.899) but significantly decreased in the late VLS group (83.455 ± 37.129 µm) compared to the control group (P = 0.003). Conclusions Melanocyte density decreased in early and late VLS. The full epidermal and cell‐layer thickness did not significantly change in early VLS, but the cell‐layer thickness decreased in late VLS.